(untitled) (Al-Mansour Journal, 2022)
Nowadays, daily communications of all kinds over the Internet have become incredibly popular. However, message transmissions over the Internet still have to face all kinds of security problems. While aim of cryptography is protecting the content of messages, steganography is the technique for hiding additional information in cover data. In this paper an embedding method in video is proposed, in which the embedded data is reconstructed without knowing the original host video or any other information about the embedding process. The proposed method enables high rate of data embedding and is robust to compression method since it works in the DCT domain. Embedding is based on AMELSBR method for compute embedded capacity per block per frame and the DCT coefficient parameter for embedding process. The selection of frame for embedding is done randomly also selection of block for actual embedding is done randomly to increase complexity and security , the embedded data was repeated before hiding in order to ensure robust extraction and reconstruction under any consideration.